Symbols in Viginia Woolf’s Novels - Knyazyan, Anna (Armenian Folia Anglistika, 2007)
Along with the development of cognitive sciences, the study of a literary text aims at broader goals than merely philological. It is connected with the revelation of individual cognitive models through traditional philological interpretation of the text. On the one hand, the basis of the interpretation of a literary text is the so-called picture of the world, which the author creates with the help of his speech, style, knowledge of historical-cultural reality, evaluations and images. On the other hand, it also includes the cognitive, ethical, aesthetic models of the perceiver which the latter applies towards the perception of the discourse, thereby ensuring the understanding of the text.The subject matter of the article is the symbol in the works of Virginia Woolf. The use of various symbols is closely connected with the aesthetic views, life experience, unique way of thinking, world vision, psychological characteristics and the literary direction of the time.Thus, the symbol is an integral part of verbal art.